Le théâtre classique français Au XVIIe siècle (Corneille et Racine) (Journal of the College of Basic Education, 2023)
The seventeenth century is one of the most important eras in the history of France. It is the era of King Louis XIV, who was surnamed as the King Sun, of absolute monarchy and of classical literature and of statesmen and grand men of literature, philosophy and arts immortalized by the history of France such as Louis XIII, Louis XIV, Richelieu, Mazarin, Corneille, Descartes, Pascal, Molière, Racine and La Fontaine.The French classic theater knew his maximum prosperity in this century and dominated the stage during the next two centuries until the literature battle of Hernani of Victor Hugo took place in the nineteenth century which marked the end of the classical period. It is said that the literature works are an expression of a moment of history and it is closely related and linked to that moment and that these actions cannot be explained without their historical contexts. The seventeenth century embodies this theory where it is difficult to understand the classic French theater without examining what were the moral, social and political lives during that century. For all these reasons we have chosen this remarkable century and in particular the tragic classical theater in the seventeenth century to be our domain of research and we did not find better than the two giants Pierre Corneille and Jean Racine to represent this theater in all its greatness and prosperity